2009
DOI: 10.1007/s00726-009-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic determination of amino acid enantiomers in bottled and aged wines

Abstract: Free L- and D-amino acids were determined by chiral GC-MS in 26 wines, comprising white wines, red wines, ice wines and sparkling wines. The aim of the work was to investigate whether quantities and pattern of D-amino acids, in particular D-proline, correlate with the storage time of bottled wines. The relative quantities with respect to the corresponding L-enantiomer ranged in white wines from 0.4 to 3.9% D-Ala, 0.9-8.3% D-Asx, and 0.5-8.9% D-Glx, in red wines from 2.9 to 10.6% D-Ala, 2.2-10.9% D-Asx, and 3.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
2
20
2
Order By: Relevance
“…1000 mg/L) could be determined [79]. That data is in rough agreement with those from European wines analyzed by direct enantioseparation using GC-MS and Chirasil-l-Val capillary columns [80].…”
Section: Plants and Plant-derived Foodstuffsmentioning
confidence: 93%
“…1000 mg/L) could be determined [79]. That data is in rough agreement with those from European wines analyzed by direct enantioseparation using GC-MS and Chirasil-l-Val capillary columns [80].…”
Section: Plants and Plant-derived Foodstuffsmentioning
confidence: 93%
“…An attempt to correlate the amount of d-amino acids with the bottling age of wines inferred earlier [173] has been reinvestigated recently [174]. It has been suggested that the presence of d-␣-amino acids in processed food can serve as an indication for 'overprocessed food' and for 'good manufacturing practice' [175].…”
Section: Racemization Studies Of ␣-Amino Acidsmentioning
confidence: 98%
“…Giuffrida et al [121] found that the pattern of release of DAAs from conventional yeast strains differ from transgenic ones. The content of several DAAs of 26 wines did not correlate with storage times [122]. Wine marinades can be used to inactivate bacteria [123] that may produce DAAs.…”
Section: 4mentioning
confidence: 99%